Corporate venturing obstacles: Sources and solutions - Sykes, Hollister B.; Block, Zenas (Journal of Business Venturing, 1989)
There is a fundamental conflict between new venture and mature company management requirements. As an enterprise evolves, the focus for success shifts from sensing and seizing opportunity to protecting and utilizing the resources that have been acquired. In surviving companies, management practices change to accommodate this changing need. The conflict arises when the mature company attempts to initiate internal new venture activities. Application of mature company practices to management of new corporate ventures is not only inappropriate, but breeds failure. To succeed with new ventures, top corporate management must first understand the inherent differences in management needs for new ventures versus the mature organization, and must then adapt a pluralistic management style that accommodates both needs. This paper examines the rationale for ten “establishment” practices and the adverse effects they can have on new ventures. From this analysis, alternative “entrepreneurial” management practices are recommended. The ten management practices examined are:(1) Enforce procedures to avoid mistakes; (2) Manage resources for efficiency and ROI; (3) Control against plan; (4) Plan long term; (5) Manage functionally; (6) Avoid moves that risk the base business; (7) Protect the base business at all costs; (8) Judge new steps from prior experience; (9) Compensate uniformly; and (10) Promote compatible individuals. Some of the adverse effects of these practices include: blockage of innovative solutions, loss of competitive lead time, entrepreneur failures, high venture failure costs, missed opportunities, fluctuating venture strategies, misread markets, reduced motivation to take risks, and loss of innovative employees. Recommended entrepreneurial management practices include: restricting “standard” procedures to those appropriate for the venture; controlling ventures by milestone planning rather than calendar budgets; being more responsive to market feedback in adjusting plans; focusing on critical issues for early determination of venture viability; assessing and choosing “affordable” risks; and making venturing a “mainstream” function of the business.